(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Modern medical education requires constant modernization and adaptation to the rapidly changing demands of clinical practice and healthcare systems. One of the most promising directions for improving the educational process is the implementation of integrated learning modules based on an interdisciplinary approach. This article aims to analyze the experience of integrating basic and clinical disciplines into unified modules and to assess their impact on the development of clinical competencies among medical students.